2012
DOI: 10.1176/appi.focus.10.1.90
|View full text |Cite
|
Sign up to set email alerts
|

Premenstrual Dysphoric Disorder: Burden of Illness and Treatment Update

Abstract: 291Five percent of menstruating women have severe premenstrual symptoms and impairment of functioning defined as premenstrual dysphoric disorder (PMDD). Clinically significant premenstrual symptoms occur in at least an additional 20% of menstruating women. The diagnosis of PMDD should be confirmed by prospective symptom charting over 2 menstrual cycles to confirm the timing of the symptoms and to rule out other diagnoses. The burden of illness of PMDD includes disruption of parenting and partner relationships … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
103
0
11

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(128 citation statements)
references
References 192 publications
(194 reference statements)
7
103
0
11
Order By: Relevance
“…In a retrospective design of PMDD assessment which is based on memory, the description of the women's mood symptoms are subjective and the recall of symptoms' severity and frequency may be amplified among these women. [27][28][29] Moreover, the responses may be associated with personality characteristics. Bailey and colleagues found that 40% of women diagnosed with PMS or PMDD also had comorbid affective or anxiety disorders.…”
Section: Prevalence Of Pmddmentioning
confidence: 99%
“…In a retrospective design of PMDD assessment which is based on memory, the description of the women's mood symptoms are subjective and the recall of symptoms' severity and frequency may be amplified among these women. [27][28][29] Moreover, the responses may be associated with personality characteristics. Bailey and colleagues found that 40% of women diagnosed with PMS or PMDD also had comorbid affective or anxiety disorders.…”
Section: Prevalence Of Pmddmentioning
confidence: 99%
“…Contraceptive pill types containing ethinyl oestradiol and drospirenone may represent another effective treatment for PMDD (2). Not all evidence supports the use of contraceptives, but they could be considered as first-line pharmaceutical interventions for women with PMDD who also require contraception (23).…”
Section: (N943)mentioning
confidence: 99%
“…PMDD is characterised by affective, cognitive, behavioural, and somatic symptoms. PMDD and PMS have a negative impact on work attendance, productivity and relationships (2). Table 1 lists the symptoms associated with these two disorders.…”
Section: Introductionmentioning
confidence: 99%
“…33 Research on PME and PMDD has found high comorbidity with anxiety disorders and worsening of anxiety symptoms. 34,35 It is possible that the presence of severe premenstrual symptoms, whether PME or PMDD, may signal an increased risk for additional vulnerabilities/comorbid symptoms that increase the complication of illness and treatment. 15 Although the relationship and underlying mechanisms of PME and PMDD are not yet fully understood, 15 they may have important similarities or differences that, once we understand them, could assist in delivering more effective treatment.…”
Section: Haley Et Almentioning
confidence: 99%